P481 Induction treatment with subcutaneous rather than intravenous ustekinumab is associated with comparable circulating drugs levels and early clinical response. (16th January 2018) - Rowan, C R; Cullen, G; Mulcahy, H; Sheridan, J; Ryan, E; De Vries, A; D'Haens, G; Doherty, G A
Abstract: Background: Ustekinumab (USK) is licenced for induction and maintenance therapy in Crohn's disease, where induction therapy is administered as a single weight-based, intravenous dose. Open-label use of USK has relied heavily on subcutaneous USK for both induction and maintenance therapy. The aim of this study was to prospectively evaluate USK trough concentrations with an exclusive subcutaneous (S/C) USK induction and corresponding clinical response. Methods: Patients with a confirmed diagnosis of Crohn's disease who provided informed consent and initiated treatment with subcutaneous USK and were included in the study. At induction patients received 360 mg USK S/C in three divided doses at Weeks 0, 1, and 2 with corresponding USK trough concentrations assessed through to Week 8. The primary outcome measure assessed was the trough serum USK levels and proportion of patients in clinical remission (defined as HBI ≤4) at Week 8 following S/C USK induction. Secondary outcome measures were trough serum USK levels at Week 1, Week 2 and changes in inflammatory markers (CRP, albumin and faecal calprotectin (FCP)) at Week 8. Results: Patient demographics and disease characteristics as per Table 1. Median Week 8 USK trough concentrations of 6.1 μg/ml (IQR 4–9.8 μg/ml) were observed and comparable to the trough of 6.4 μg/ml (IQR 3.3–9.6 μg/ml) observed following 6 mg/kg IV induction treatment in the UNITI studies. There was no significant difference in Week 8 trough concentrations when comparing those patients treated with and without concomitant immunomodulators (6.25 μg/ml, IQR 4.38–9.28; 5.8 μg/ml, IQR 4.1–9.9, respectively; p = 0.658). 84.2% (16 of 19) of patients were in clinical remission (HBI ≤4) by Week 8. There was a significant improvement in HBI scores from Week 0 to Week 8 (median HBI 5 vs. median HBI 1, p = 0.002). A significant improvement in FCP was also noted; median FCP 533 μg/g vs. 278 μg/g ( p = 0.038). Conclusions: USK trough concentrations with an exclusive SC USK induction treatment are comparable to those observed with IV induction and are associated with early improvement in symptoms and inflammatory markers. These results support the use of SC as an alternative to IV induction in CD in situations where access to infusion therapy is a barrier to timely treatment.